Public Trust: Indonesian Policy in Developing a New Capital City (IKN) - Rifaid Rifaid; M. Taufik Rachman; Tawakkal Baharuddin; Srirath Gohwong (Journal of Governance and Public Policy, 2023)
Public trust is a key factor in assessing government policies, as it strengthens the connection between the state, government, and society, forming the basis for successful policy implementation. This study investigates public trust in the development of Indonesia’s new capital city (IKN), employing a qualitative approach with descriptive content analysis. Twitter discussions on IKN policies were analyzed using Nvivo 12 Plus software. The findings reveal that public trust in IKN development is generally positive, driven by the vision of IKN as a future model world city, promoting economic equality and prosperity. President Joko Widodo’s leadership also plays a pivotal role. However, concerns about environmental damage and budgetary issues have contributed to a decline in trust. The study concludes that public trust will be critical to the long-term sustainability of IKN development. This research advances the field by integrating social media analytics, particularly Twitter discussions, with public policy analysis, offering real-time insights into public sentiment toward major government projects like IKN. The novelty of this study lies in its examination of public trust specifically in the context of developing a new capital city, a rare topic within existing literature. This study contributes to the broader discourse on public trust and policy implementation by providing a unique case study on IKN. It highlights the factors that enhance and diminish public trust in large-scale government projects, offering policymakers insights on how to address concerns and build sustained trust, which is crucial for the project's future success.